Dependence structure between energy uncertainty index and airlines stocks returns and volatility: A short communication - Yifei Cai; Yahua Zhang; Tsangyao Chang (Transport Economics and Management)
This study evaluates the performance of interlinks between energy uncertainty index and airlines stock returns and volatility by applying the wavelet coherence analytical methodology. For stock returns, American Airlines exhibits notable lead-lag effects, while Air China and Air France show varied patterns. In terms of volatility, American Airlines' volatility aligns with energy uncertainty across phases. Air France's volatility both leads and lags, and Air China shows minimal co-variation. The policy implications are provided at the end of the study.